RAJYA RAJYA ING JAWA MADHYA, RAJA-RAJA MATARAM KUNA ABAD 9-10 MASEHI: PERBANDINGAN ANTARA NASKAH PUSTAKA RAJYA-RAJYA I BHUMI NUSANTARA DENGAN PRASASTI WANUA TENGAH III - Kayato Hardani (BRIN, 2010)
Pustaka Rajya Rajya has become a controversial text in Indonesian historiography. Some experts including philologists, archaeologists, and historians are still having strong arguments on the authenticity of the text. Pustaka Rajya are indeed an interesting text to be examined. Among others, Pustaka Rajya told 'a fantastic' story, on the History of Ancient Mataram Kings. In other hand, we also found another authentic historical source, Wanua Tengah Ill inscription. This copper inscription also contains a 'short story' about ancient Mataram kings. Therefore, in this article informations from the two sources will be compared. The result shows how the 'writer in the past' has written 'his own past'.